1963
DOI: 10.1111/j.1479-828x.1963.tb00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Renal Disease A Ten‐Year Survey

Abstract: IN recent years there has been an increased awareness of the problem of renal disease complicating pregnancy. The importance of latent pyelonephritis, particularly in women of the childbearing period, is being realized, as well as the relationship of renal disease to pre‐eclampsia and hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 26 publications
0
28
1
1
Order By: Relevance
“…Excluding the therapeutic abortions, the 76% fetal sur vival was substantially higher than previously reported [1][2][3] and was slightly lower than that observed in a large retrospective series of women with glomerular disease without overt renal insufficiency [7]. Five of the 15 fetuses who reached a viable gestational age were small for date, but only 2 of them were lost because of severe intrauterine growth retardation.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…Excluding the therapeutic abortions, the 76% fetal sur vival was substantially higher than previously reported [1][2][3] and was slightly lower than that observed in a large retrospective series of women with glomerular disease without overt renal insufficiency [7]. Five of the 15 fetuses who reached a viable gestational age were small for date, but only 2 of them were lost because of severe intrauterine growth retardation.…”
Section: Discussionmentioning
confidence: 45%
“…Fetal losses as high as 79% have been reported in this condition [1,2] and it has been suggested that pregnancy may promote a rapid worsening of renal function leading to terminal renal failure [3]. However, only incomplete information about the natural history of the renal disease before pregnancy is available in these reports.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Early studies [1][2][3][4] sug gested the prognosis was unfavorable; however, more recent evidence suggests that, in the absence of decreased renal function or severe hypertension, the incidence of major complications is minimal and survival is good [5][6][7][8][9][10]. In women with glomerular disease who have normal renal function and normal blood pressure, the only signif icant risk factor associated with pregnancy is an increased risk of preeclampsia and the ultimate prognosis is un changed when compared to normal pregnant women.…”
Section: Introductionmentioning
confidence: 99%